DIET DEVELOPMENT FOR MUD CRAB (Scylla serrata) AQUACULTURE USING LOCAL MATERIAL AVAILABLE IN CENTRAL JAVA - Johannes Hutabarat (JOURNAL OF COASTAL DEVELOPMENT, 1999)
Phase I study (1996/1997) indicated that the local protein materials at relatively low cost were found abundance in Central Java throught the year. Their nutritional levels i.e. protein content, amino acids profile and availability are suitable to be used for mud-crab feed development. It is therefore the selected protein materials such as : soybean, mysidaceae, trash fish and saga, are then subjected to the formulation of experimental diet for mud crab on-growing culture (Phase II study 1997/1998) The aims of study are to determine the nutritional performance of experimental diets (novel diets) for mud-crab scylla growth, food utilization and protein efficiency during the feeding trial. The study has been conducted in a 12 bamboo-cages of 1.0 x 0.5 x 0.70 m immersed in BW ponds at CZEL “Prof. Gatot Rahardjo J.S – UNDIP”, Jepara and the stocking density of wild mud-crab (50-60 gram) was 1 pieces /box (0.2 x 0.2 m). Experimental diet (pellet formed) consists of four treatments i.e. diet A (25% dietary protein level), diet B (30%), diet C (35%) and diet D (40%). The growth and nutritional parameters observed as response to the experimental diets tested are : Individual growth and growth increment, Specific Growth Rate (SGR), FCR, NOU amd PER. The completely Randomize Design was adopted in this study and then followed by Duncans’s New Multiple Range Test in order to determine the difference among the treatments. The results derived from this study indicated that diet C (dietary protein level of 30%) appeared to be the best diet wheather for the growth (W and SGR0 or nutritional performance (FCR, PER, and NPU) and followed by diet B, D and A. Meanwhile, during the course of feeding trial water quality of experimental media remain in good condition to support ud-crab growth.